Financial Technology For SMEs Capital Problems With Crowdfunding Method - Mappa Panglima Banding; Ashar Ashar; Ahmad Juliana; Muh. Irfandy Azis; Yohanna Thresia (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
This study motivated by Micro, Small, and Medium Enterprises (SMEs) problem. SMEs still have difficulty accessing financial institutions. This problem should overcome when SMEs utilize information technology in business management such as crowdfunding features through Financial technology, where crowdfunding has known as a funding offering facility for social interests. The study is a qualitative descriptive analysis. This study intended to decide how to use crowdfunding-based financial technology by SME's at Tarakan City. The experiment subject is a randomized participant of 15 participants based on a predetermined category faced with stakeholders SME’s at Tarakan City. The data consisted of primary data non-metric or qualitative data. Participants were interviewed and examined to learn about the use of crowdfunding-based financial technology by small and medium-sized companies in Tarakan City, followed by triangulation with three models, i.e. data triangulation, investigator triangulation, and methods triangulation. Then analyzed with an interactive model through data reduction, data display, and conclusion drawing procedures. The result of the research shows that from the 15 informants in this study, there were only two informants who knew about Financial technology, and only a small proportion of SMEs at Tarakan City able to utilize Financial technology based on crowdfunding for their funding needs and use crowdfunding for working capital.